Pengaruh Variasi Dimple Intake Manifold pada Water Injection System di Mesin 100cc Berbahan Bakar LPG Terhadap Konsumsi Bahan Bakar Spesifik - Warit Abi Nurazaq; Mulyono, Novangga Adi; Reynaldi Akbar Ali; Sihmaulana Dwianto (P3M Politeknik Negeri Jember, 2025)
The number of motorized vehicle users in Indonesia is increasing. Alternative fuels are needed to meet the needs of these motorized vehicles. One of the alternative fuels that can be used is LPG. However, in its application in motorized vehicles, LPG fuel has a weakness, namely that the engine temperature tends to be higher, thus affecting the performance and specific fuel consumption produced. One additional mechanism that can be used to optimize the use of LPG fuel in motorized vehicles is the water injection system. The addition of a water injection system to motorized vehicles is able to maintain the temperature of the combustion chamber, so that it can improve the results of specific fuel consumption. To optimize the use of the water injection system in motorized vehicles, variations in the surface of the intake manifold can be used, namely standard intake, tight dimple and loose dimple. The use of this variation is expected to make the fuel mixture and water injection mix perfectly before entering the combustion chamber. The results of the data collection that have been carried out show that the lowest specific fuel consumption (SFC) is obtained by using a tight dimple intake manifold with water injection with an average value of 0.015882797 kg/HP.hour at an engine speed of 8000 RPM.